Potensi ekonomi sirkular dalam pengembangan klaster industri daur ulang kapal di indonesia - Sunaryo Sunaryo; Aufa Rahma Asyifa; Wanginingastuti Mutmainnah; Hariyanto (Prosiding SNTTM, 2025)
The objective of the research is to investigate the potential of circular economics in the development of the national ship recycling industry cluster. In conjunction with the entry into force on 26 June 2025 of the Hong Kong International Convention for the safe and environmentally sound recycling of ships, which establishes mandatory regulations to govern the way ships are recycled, modern ship recycling facilities are also growing in Indonesia. This growth is mainly due to the constant increase of uneconomical and old national shipping fleet. Which needs to be renewed and sent to the ship recycling facilities, due to the impact of the Cabotage principle, and due to high demand for raw materials from the iron and steel industry. in modern ship recycling activities, which comply with the regulations of the Hong Kong Convention, the "3 Rs" (recycle, reuse, and reduce) processes are realized, i.e., scrapped metal materials will be used as raw materials by the steel industry. ship structure and components, which are still in good condition, can be used by ship repair yards and other uses, and hazardous wastes are properly handled and treated. which will protect the environment from pollution, and indirectly reduce deforestation from ore mining. The potential circular economics could be realized by the networking of the ship recycling activities, which include: ship recycling yards, shipping companies, steel industry, ship repair yards, waste treatment facilities, and related institutions, which can be integrated into a ship recycling industry cluster.